2013
DOI: 10.1210/er.2013-1012
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Glucocorticoid Exposure: The Hypothalamic-Pituitary-Adrenal Axis, Placental Function, and Long-term Disease Risk

Abstract: An adverse early-life environment is associated with long-term disease consequences. Adversity early in life is hypothesized to elicit developmental adaptations that serve to improve fetal and postnatal survival and prepare the organism for a particular range of postnatal environments. These processes, although adaptive in their nature, may later prove to be maladaptive or disadvantageous if the prenatal and postnatal environments are widely discrepant. The exposure of the fetus to elevated levels of either en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
149
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 402 publications
(430 reference statements)
6
149
0
Order By: Relevance
“…Importantly, life-span effects are influenced by developmental programming by challenges such as altered F 1 nutrition during their development. The mechanisms are likely multiple and include both programmed changes within the hypothalamo-pituitary adrenal axis (Braun et al 2013;Zambrano et al 2014) and altered peripheral production of glucocorticoids in adipose tissue that are influenced by maternal nutrition (Guo et al 2013). The influence of developmental programming is clearly shown by the difference in the corticosterone concentrations in the F 1 from control and obese mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, life-span effects are influenced by developmental programming by challenges such as altered F 1 nutrition during their development. The mechanisms are likely multiple and include both programmed changes within the hypothalamo-pituitary adrenal axis (Braun et al 2013;Zambrano et al 2014) and altered peripheral production of glucocorticoids in adipose tissue that are influenced by maternal nutrition (Guo et al 2013). The influence of developmental programming is clearly shown by the difference in the corticosterone concentrations in the F 1 from control and obese mothers.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published Rodriguez et al 2012;Vega et al 2015;Zambrano and Nathanielsz 2013) that a, e Represent a normal; b, f a premature; c, g an augmented; and d, h a premature and augmented aging process maternal serum corticosterone concentrations in maternal obesity (MO) were higher than controls (C) at the time of breeding, end of gestation, 19 days gestation (dG), and end of lactation, postnatal day (PND) 21. Prenatal exposure to increased levels of glucocorticoids changes hypothalamic pituitary adrenal axis function (Braun et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, both fetal and neonatal IGF-I circulating levels are correlated with BW (Lassarre et al, 1991). The reciprocal interactions between the GH/IGF and the HPA axis are well documented (Neggers and van der Lely, 2011;Mazziotti and Giustina, 2013), including during fetal development (Braun et al, 2013), but little is known on the relationships between cortisol and IGF-I in juvenile pigs. We show here that CBG may play an important role in these relationships with a strong sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability may be conferred through the fine-tuning of stress-regulatory systems that occurs following exposure to insults during a sensitive period in utero or early postnatal life (Van den Bergh, 2011). To date, human and animal evidence has convincingly reported that exposure to excess cortisol and maternal prenatal psychological distress (i.e., an amalgamation of comorbid subjective stress, anxiety, and depressed mood) alters the function of one of the co-acting stress-regulatory systems--the hypothalamic-adrenal-pituitary (HPA) (Braun et al, 2013;Field, 2011;Kajantie, 2006;Seckl and Holmes, 2007). Relatively less attention has been paid to the influences of prenatal maternal cortisol and psychological distress on the second stress-regulatory system (i.e., the autonomic nervous system; ANS).…”
Section: Introductionmentioning
confidence: 99%